Handbook of hygiene control in the food industry - Lelieveld, H. L. M.; Holah, J. T.; Gabrić, Domagoj, 1981- (Elsevier, Woodhead Publishing, 2016)
"Handbook of Hygiene Control in the Food Industry, Second Edition, continues to be an authoritative reference for anyone who needs hands-on practical information to improve best practices in food safety and quality. The book is written by leaders in the field who understand the complex issues of control surrounding food industry design, operations, and processes, contamination management methods, route analysis processing, allergenic residues, pest management, and more. Professionals and students will find a comprehensive account of risk analysis and management solutions they can use to minimize risks and hazards plus tactics and best practices for creating a safe food supply, farm to fork. Presents the latest research and development in the field of hygiene, offering a broad range of the microbiological risks associated with food processing Provides practical hygiene related solutions in food facilities to minimize foodborne pathogens and decrease the occurrence of foodborne disease Includes the latest information on biofilm formation and detection for prevention and control of pathogens as well as pathogen resistance."--Resumé vydavatele
Keywords: potravinářský průmysl -- hygienické aspekty; potravinářská technologie -- hygienické aspekty; bezpečnost potravin; hygiena potravin; kontrola potravin; food industry -- hygienic aspects; food technology -- hygienic aspects; food safety; food hygiene; food quality control; kolektivní monografie; elektronické knihy; collective monographs; electronic books